The Academic Failure Model of the Senior Students of Mazandaran Province based on the Socio-Economic Position and Family Social Capital with the Mediation of Family Chaos - Salehi, Mehrdad; Pahlavan, Manouchehr; Shojaee, Ali Asghar (Iranian Journal of Educational Sociology, 2022)
Purpose: Today, the issue of academic failure is one of the most important and scrutinized factors in educational systems and examining the effective factors on it can help in better understanding this phenomenon and providing solutions to its reduce. Therefore, the current research was conducted with the aim of modeling the academic failure of senior students based on the socio-economic position and family social capital with the mediation of family chaos. Methodology: This study in terms of purpose was applied and in terms of implementation method was quantitative from type of correlational. The population of the present research was the senior students of Mazandaran province, which 170 people of them were selected as a sample by cluster sampling method. The research tool was a researcher-made questionnaire of effective social factors on academic failure, which had four components of academic failure, socio-economic position, family social capital and family chaos. The face validity of the questionnaire was confirmed by education specialists and experts and its reliability was obtained with Cronbach's alpha method above 0.70. The data were analyzed with tests of regression and structural equation modeling from type of path analysis in SPSS and LISREL software. Findings: The findings showed that all three variables of socio-economic position, family social capital and family chaos separately had a significant correlation with the academic failure of senior students and were able to predict the 31.0%, 20.2% and 22.9% of the changes of their academic failure, respectively. Also, all the three mentioned variables together could predict 51.6% of the changes of academic failure of senior students. In addition, the academic failure model of senior students based on the socio-economic position and family social capital with the mediation of family chaos had a good fit, and in this model, the variables of socio-economic position and family social capital on family chaos and academic failure and the variable of family chaos on academic failure had a direct and significant effect and the variables of socio-economic position and family social capital with the mediation of family chaos had an indirect and significant effect on academic failure (P